Synthesis and Catalytic Activity of Crown Jewel‐Structured (IrPd)/Au Trimetallic Nanoclusters. (16th December 2014) - Zhang, Haijun; Lu, Lilin; Kawashima, Keisuke; Okumura, Mitsutaka; Haruta, Masatake; Toshima, Naoki
<x xml:space="preserve">Abstract</x> Crown‐jewel‐structured (IrPd)/Au trimetallic nanoclusters are prepared by a galvanic replacement reaction using Ir/Pd nanoclusters with a structure of Ir rich in the core and Pd rich in the shell as mother clusters. The catalytic activity of the top Au atoms for aerobic glucose oxidation of the trimetallic nanoclusters is the highest ever reported among all supported and colloidal catalysts. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>